Pengaruh Belanja Pemerintah Daerah dan Pembangunan Infrastruktur Terhadap Pertumbuhan Ekonomi di Kab./Kota di Provinsi Sumatera Barat - Rana Yolanda; Rini Elvira (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Local government spending and infrastructure development are expected to have a significant impact on economic growth, but the impact may vary across regions in Indonesia. The aim of this research is to determine the impact of local government spending and infrastructure development on economic growth in districts/cities in West Sumatra. This research methodology uses a quantitative approach using associative techniques. The analysis methodology for this research includes data adequacy tests, classical assumption tests, multiple linear regression tests, and adjusted R-squared tests. The research results show that regional government spending (X1) has no significant effect (0.426>α0.05). Opposite to economic growth (Y). There is also no significant influence on infrastructure development (X2) (0.128>α0.05). Meanwhile, the variables "Local government spending" and "Infrastructure development" do not simultaneously influence economic growth, with a calculated F value of 0.415 < F > 0.05. With an adjusted R-squared value of 0.15, this means that the contribution of the independent variables in this research to the economic growth of districts/cities in West Sumatra is 1.5%. Therefore, it can be concluded that H3 is rejected. Studies on regional government spending generally show that partial or simultaneous infrastructure development does not affect economic growth in districts/cities in West Sumatra.